Presence of Rhodnius neglectus Lent, 1954 (Hemiptera: Reduviidae: Triatominae) in Araraquara, São Paulo, Brazil: signals the importance of surveillance for the municipality - Santana, Jociel Klleyton Santos [UNESP]; Belintani, Tiago [UNESP]; Rosa, Joao Aristeu da [UNESP]; Oliveira, Jader de (Soc Chilena Entomologia, 2024)
Several publications have reported the occurrence of triatomines in urban areas of the Americas. Four species of triatomines are reported in the municipality of Araraquara, S & atilde;o Paulo, Brazil: Panstrongylus megistus, Rhodnius neglectus, Triatoma infestans, and T. sordida. Although already notified to the municipality, we present the record of household invasion by R. neglectus in urban area in the Araraquara. This occurrence reinforces the concern over urbanization by R. neglectus in the state of S & atilde;o Paulo, with reports of colonization and home invasion in various municipalities.
Keywords: Chagas disease; invasion; kissing bugs; vectors; urban areas